Characteristic of White Glutinous Sticky Rice “Kipang” added by Coconut Dregs - Kesuma Sayuti; C,W Refdi; P Ramadani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
This study aimed to determine the effect of coconut dregs addition on white glutinous sticky rice “Kipang” characteristics. The study used a CRD with six treatments and three replications. The treatments applied in this study is coconut dreg, consisting of A (0%), B (5%), C (10%), D (15%), E (20%), and F (25%). The data were analyzed using ANOVA and subsequently subjected to DNMRT at the 5% significance level. The study showed that adding coconut dreg affected moisture content, protein, fat, carbohydrates, crude fiber, total sugar, and organoleptic acceptance such as color, taste, and crispiness. However, it did not significantly affect the ash content and the organoleptic acceptance of the aroma. The best treatment was F product (25%) with moisture content (6.44%), ash content (0.93%), fat content (13.4%), protein content (3.17%), carbohydrates content (75.73%), crude fiber (4.47%), total sugar (42.88%) and organoleptic acceptance for color 4.43 (like), aroma at 4.23 (like), taste 4,33 (like) and fragility at 4.23 (like). The glycemic index of the product was (67.92%)